The Implementation of Flashcard Media in Early-Grade Learning: A Case Study on Strengthening Students’ Understanding of Fundamental Mathematical Concepts at MI Al Magfiroh - Khoiriyah Muzakki; Moh Sutomo; Indah Wahyuni (FKIP - Universitas Riau, 2026)
Learning in the early grades of Madrasah Ibtidaiyah requires instructional strategies and media aligned with students’ developmental characteristics, as they are still in the concrete operational stage. Verbal and monotonous teaching can reduce students’ interest, motivation, and understanding of basic mathematical concepts. Therefore, visual instructional media such as flashcards offer a relevant alternative to promote active and meaningful learning. This study aims to describe the implementation of flashcard media and examine its impact on learning mathematics, particularly place value concepts, among first-grade students at MI Al Magfiroh. The research employed a qualitative descriptive case study design. Data were collected through classroom observations, semi-structured interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that flashcard media created an active, collaborative, and student-centered learning environment. Students engaged directly in observing, manipulating, and discussing the materials, which facilitated concrete conceptual understanding. Moreover, flashcards increased students’ motivation, interest, social interaction, and self-confidence. Overall, flashcard media proved effective in supporting early-grade mathematics learning consistent with students’ developmental needs.